Remimazolam’s clinical application and safety: A signal detection analysis based on FAERS data and literature support - Gang Ye; Luqin Ding; Qingbo Zhou (PLoS ONE, 2025)
This study aimed to evaluate the adverse event profile of remimazolam, a novel ultra-short-acting benzodiazepine, with a focus on its safety in the respiratory, cardiovascular, and immune systems across diverse patient populations. We analyzed adverse event reports from the FAERS database over a defined period, performing signal detection using the proportional reporting ratio (PRR) and the reporting odds ratio (ROR), and contextualized the findings with a concurrent literature review. Remimazolam demonstrated a strong signal for hypoventilation. In the cardiovascular system, it was associated with serious adverse events, including cardiac and cardiorespiratory arrest, particularly in high-risk patients. Furthermore, we detected significant signals for severe hypersensitivity reactions, such as anaphylactic shock and laryngeal edema, while signals in other systems were less pronounced but remained clinically significant. Given that the study population was predominantly elderly, and considering the serious nature of the identified signals, its potential for adverse events necessitates vigilant monitoring. Future research should focus on clarifying risks within specific high-risk groups to establish optimized safety protocols.